COVID-19, nationwide lockdown, and migrant workers: A study from eastern India - Rabiul Ansary; Mohammad Izhar Hassan (National Geographical Journal of India, 2023)
Being the second largest populous country in the world, India reports a volume of internal migration that is as large as the population of European Union. This poses a serious challenge before the policy makers in fight against contagious virus like Covid-19. The nation-wide lockdown led to panic, and thousands of migrant workers and their dependents began a march on foot towards their native place located hundreds of kilometres away. And what followed is huge human suffering including loss of life. Results suggest that male migrants accounted for around 92 percent (3.3 million) of the total work/employment-related migration from the eastern region. Work or employment-related reasons account for about 55 percent of males out-migrating from the region to other parts of the country. In terms of absolute size, Bihar is the largest source of migrant workers, followed by West Bengal and Odisha. Bihar alone contributes as much as 65 percent of all male out-migrants from the region for work or employment. Taking out-migration from eastern India as a case, an attempt is made here to looks into the vulnerability of migrant workers, and to critically evaluate the government approach to address the crisis.